RELIGIOUS ACTIVITIES AND PANCASILA STUDENT PROFILE IN STRENGTHENING CHARACTER EDUCATION - Luthfi Adnan; Nurul Fadlilah; Ahmad Jauhar Fuad (Jurnal Konseling Pendidikan Islam, 2026)
The Pancasila Student Profile, initiated by the Indonesian Ministry of Education and Culture, aims to shape students who are not only intellectually capable but also spiritually and morally grounded. One of the core elements of this profile is developing faith in God Almighty, religious devotion, and noble character. In the face of increasing challenges in education, teacher creativity plays a vital role in fostering effective, inspiring, and meaningful learning experiences. This study, entitled "The Relevance of Religious-Based Activities to the Pancasila Student Profile Element: Faith in God Almighty, Devotion, and Noble Character in Strengthening Character Education at SMP IT Al-Mubarok Kras Kediri", adopts a qualitative descriptive approach. The purpose of this research is to explore how religious-based activities contribute to character formation aligned with the Pancasila Student Profile.The findings reveal that: (1) Religious activities at SMP IT Al-Mubarok are systematically implemented through daily, weekly, and incidental programs; (2) The implementation faces several challenges, such as diverse student backgrounds and limited parental involvement; (3) These religious-based activities are highly relevant and supportive of the Pancasila Student Profile, particularly in strengthening students’ faith, religious devotion, and moral character.This study emphasizes the importance of religious education as a foundation for character development and recommends strengthening religious-based programs through integrated collaboration among schools, teachers, and parents.